Comparison of glycated albumin and hemoglobin A(1c) levels in diabetic subjects on hemodialysis - Peacock, T P; Shihabi, Z K; Bleyer, A J; Dolbare, E L; Byers, J R; Knovich, M A; Calles-Escandon, J; Russell, G B; Freedman, B I (Kidney international, 2008)
Glycated albumin is thought to more accurately reflect glycemic control in diabetic hemodialysis patients than hemoglobin A(1c) because of shortened red cell survival. To test this, glycated hemoglobin and albumin levels were measured in blood samples collected from 307 diabetic subjects of whom 258 were on hemodialysis and 49 were without overt renal disease. In diabetic subjects with renal disease, relative to those without, the mean serum glucose and glycated albumin concentrations were significantly higher while hemoglobin A(1c) tended to be lower. The glycated albumin to hemoglobin A(1c) ratio was significantly increased in dialysis patients compared with the controls. Hemoglobin A(1c) was positively associated with hemoglobin and negatively associated with the erythropoietin dose in hemodialysis patients, whereas these factors and serum albumin did not significantly impact glycated albumin levels. Using best-fit multivariate models, dialysis status significantly impacted hemoglobin A(1c) levels without a significant effect on glycated albumin. Our results show that in diabetic hemodialysis patients, hemoglobin A(1c) levels significantly underestimate glycemic control while those of glycated albumin more accurately reflect this control.